Herpetofauna en varillal alto seco del tramo puesto de vigilancia Irapay - comunidad Mishana en la Reserva Nacional Allpahuayo Mishana, Loreto - Perú - Arevalo Pacaya, Luis Fernando (2023)
From March to July 2022, the herpetofauna was studied in the high dry varillal of the Allpahuayo Mishana National Reserve, between the Irapay surveillance post (km 28 of the Iquitos-Nauta highway) and the Mishana community. The method used was the linear transect, recognition by visual encounter and chance encounters. A specific richness of 15 amphibian species and 17 reptile species is reported. In the high dry varillales the densities were low for amphibians and reptiles (less than one individual per km2); in amphibians, Ranitomeya reticulata reports a density of 0.105 ind/km2 and in reptiles Kentropyx pelviceps reports 0.45 ind/km2, while Stenocercus fimbriatus, 0.3 ind/km2. The flora of the varillales where the herpetofauna interacts was made up of 59 families of plants with 173 species (considering the 4 selected dry high varillals). The plants were composed by Fabaceae (21 species), Chrysobalanaceae (10 species), Lauraceae (9 species), Rubiaceae, Sapotaceae, Apocinaceae and Euphorbiaceae with 8 species respectively, Anonaceae, Myrtaceae and Clusiaceae. It is concluded that the specific richness of the herpetofauna is low and medium, and its composition in the dry high varillal of the Irapay-Mishana community surveillance post section, expressed in similarity, is low.